Modelo de maturidade de sistema de gestão integrado para laboratórios de ensaio e calibração - Gerônimo, Bruna Maria (2023)
The test and calibration laboratories are undergoing an organizational restructuring due to technical and regulatory requirements, which implies a reorganization of their management systems (MS). To help these laboratories, maturity models (MMs) can be used for the implantation and maintenance of SG, since they are tools used to evaluate the current capabilities of organizations and enable the implementation of changes in a structured way. The use of fuzzy logic is often found in association with the construction of MMs, along with multicriteria decision-making methods. Fuzzy logic assists in the construction of MMs, removing subjective elements from the maturity assessment. The multicriteria methods, on the other hand, allow a classification and ranking of alternatives, which allows the user to make a more assertive decision. Despite the existence of MMs aimed at SGs, there are no studies on MMs aimed at testing and calibration laboratories that use fuzzy logic and multicriteria decisionmaking methods. Thus, the present study aims to propose a descriptive MM of an SGI - Integrated Management System - for testing and calibration laboratories. The SGI was built using the standards ABNT NBR ISO/IEC 17025 - General requirements for the competence of testing and calibration laboratories, ABNT NBR ISO 14001 - Environmental management systems - Requirements with guidelines for use and ABNT NBR ISO 45001 - Management systems occupational health and safety - Requirements with guidance for use. For the construction of the MM, the VIKOR multicriteria decision support method was adopted, along with fuzzy logic. When applying the MM, the result obtained corresponds to the distancing of the current situation of the laboratory in relation to an ideal positive scenario, about compliance with the integrated requirements of the standards. After its development, this MM was partially tested and validated. Thus, it is expected that the proposed MM will allow the assessment of the laboratories' maturity, helping managers to continuously improve their laboratory activities and processes. In this way, it could be concluded that the objective outlined was achieved, thus contributing to the development and advancement of science. It is suggested, for future work, the implementation of this MM in testing and calibration laboratories that have an SGI based on the referred standards.